Gas erleuchtet die Schweiz. Stadtgas als Energieträger des 19. und 20. Jahrhunderts - Maximilian Oswald (Historia.scribere)
Gas is an energy carrier, which fundamentally changed the way we consume  energy. This paper will describe its history with focus on the development of town gas at Switzerland and its biggest city Zurich. The problems and the challenges, the gas industry had to face during its existence – especially concerning the establishment of electricity as a      competitor on the energy market – will thoroughly be discussed.